Counter-cyclical fiscal rules and the zero lower bound - Hauptmeier, Sebastian,Kamps, Christophe,Radke, Lucas (European Central Bank, 2022)
We analyse the effectiveness of optimal simple and implementable monetary and fiscal policy rules in stabilising economic activity, inflation and government debt in face of an occasionally binding lower bound on the nominal interest rate in a New Keynesian model. We show that, within the traditional assignment of active monetary policy and passive fiscal policy, the optimal fiscal policy rule features a strong counter-cyclical response to the deviation of inflation from the central bank's target - providing significant macroeconomic stabilisation especially at the lower bound - while also featuring a strong response to government debt. Our quantitative results show that the optimal counter-cyclical fiscal feedback to inflation significantly improves welfare and reduces the lower-bound frequency. In addition, the optimal simple monetary and fiscal rules almost completely resolve the deflationary bias associated with the lower bound.
10.2866/887345
Keywords: Graue Literatur; Fiscal Rules; Zero Lower Bound; Inflation Targeting; Deflationary Bias